The frequency of chemotherapy induced amenorrhea in premenopausal patients with breast cancer in the Ayatollah Rohani hospital of Babol - Mohammad Ranaei; Mohsen Vakili Sadeghi; Mohammad Hossein Taghvaei (Mashhad University of Medical Sciences, 2021)
Introduction: Breast cancer is the most common cancer in women worldwide. One of the late and long-term complications of chemotherapy regimens used in the treatment of these patients is chemotherapy induced amenorrhea (CIA). Studies have shown that CIA improves prognosis in breast cancer patients with positive estrogen receptor. So, this study was performed with aim to determine the frequency of CIA in patients with breast cancer. Methods: This retrospective descriptive-analytical study was performed on 96 premenopausal breast cancer patients aged less than 50 years old who underwent chemotherapy in Ayatollah Rohani Hospital of Babol during 2009_2015. Chemotherapy regimens include six cycles of adriamycin and cyclophosphamide (AC) per two weeks or four cycles of AC followed by four cycles of one taxane. Demographic data of the patients, date of amenorrhea and return of menstruation, chemotherapy regimen, size of tumor and number of metastatic lymph nodes were collected by researcher-made questioner and were analyzed with SPSS software (version 18) and T-test and Chi-square test. Results: In this study, 96 patients (37.5%) had age of ≤40 years and 60 patients (62.5%) aged 40-50 years. Fifty eight patients (60.4%) experienced chemotherapy-induced amenorrhea. 44 subjects (73.3%) of patients aged 40-50 years and 14 (38%) of those aged < 40 years experienced CIA (p=0.001). CIA was 61% in AC regimen and was 59.5% in AC and taxane regimen (p=0.87). Conclusion: CIA is common that is more common in patients older than 40 years. Addition of taxane to anthracycline-based chemotherapy regimen didn't increase CIA.